2015
DOI: 10.1002/mc.22291
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of ALDH+ breast tumor initiating cells by docosahexanoic acid and/or gamma tocotrienol through SHP-1 inhibition of Stat3 signaling

Abstract: Study investigated the ability of docosahexaenoic acid (DHA) alone and in combination with gamma-tocotrienol (γT3) to eliminate aldehyde dehydrogenase positive (ALDH+) cells and to inhibit mammosphere formation, biomarker and functional assay for tumor initiating cells (TICs), respectively, in human triple negative breast cancer cells (TNBCs), and investigated possible mechanisms of action. DHA upregulated Src homology region 2 domain-containing protein tyrosine phosphatase-1 (SHP-1) protein levels and suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…STAT3 inhibition in cancer cells appeared to be involved in the apoptotic process promoted by DHA, as STAT3 de-phosphorylation was associated with cancer cell death and treatment with a phosphatase inhibitor inhibited the cancer cell death. Our findings are consistent with previous data, showing the capability of DHA to inhibit STAT3 in other tumor cell models [54, 55]. Moreover, new data have shown that STAT3 inhibitors, in combinatorial therapy with anthracycline-based immunogenic chemotherapy, potentiated the immunogenic chemotherapy [32].…”
Section: Discussionsupporting
confidence: 93%
“…STAT3 inhibition in cancer cells appeared to be involved in the apoptotic process promoted by DHA, as STAT3 de-phosphorylation was associated with cancer cell death and treatment with a phosphatase inhibitor inhibited the cancer cell death. Our findings are consistent with previous data, showing the capability of DHA to inhibit STAT3 in other tumor cell models [54, 55]. Moreover, new data have shown that STAT3 inhibitors, in combinatorial therapy with anthracycline-based immunogenic chemotherapy, potentiated the immunogenic chemotherapy [32].…”
Section: Discussionsupporting
confidence: 93%
“…Pece et al, [41] have shown that PKH26 dye retention can be used to visualize and distinguish tumor stem cells in situ among the population of more actively proliferating cells. Note that although SUM159 is triple negative, highly undifferentiated, and stem-like in nature, it is still hierarchically organized, and only a small proportion of the cells within the population are actually stem cells [42, 43]. …”
Section: Resultsmentioning
confidence: 99%
“…In fact, DSF-induced suppression of CSCs has been extensively studied and well-recognized [23]. Meanwhile, in vitro and/or in vivo studies have confirmed that DHA also possesses the potential to eliminate CSCs [5558]. Therefore, mammosphere formation and ELDA assay were applied to test whether DSF's inhibitory action on CSCs is enhanced by DHA.…”
Section: Discussionmentioning
confidence: 99%